From pink to blue and back to pink again: changing the Co(ii) ligation in a two-dimensional coordination network upon desolvation. Issue 3 (17th December 2015) - Chisca, Diana; Croitor, Lilia; Coropceanu, Eduard B.; Petuhov, Oleg; Baca, Svetlana G.; Krämer, Karl; Liu, Shi-Xia; Decurtins, Silvio; Rivera-Jacquez, Hector J.; Masunov, Artëm E.; Fonari, Marina S.
Abstract : Heating of a pink 2D Co(ii ) complex initiates a single-crystal-to single-crystal (SC–SC) transition to a blue complex. Abstract : Heating of a pink two-dimensional Co(ii ) coordination network [Co2 (μ2 -OH2 )(bdc)2 (S-nia)2 (H2 O)(dmf)]·2(dmf)·(H2 O) n (1 ) built from 1, 4-benzenedicarboxylic acid (H2 bdc) residues and thionicotinamide (S-nia) ligands initiates a single-crystal-to-single-crystal transition accompanied by removal of both coordinated and co-crystallized solvents. In the dry blue form, [Co(bdc)(S-nia)] n (dry_1 ), the Co(ii ) centers changed from an octahedral to a square pyramidal configuration.